Active Learning to Improve Teachers’ Competence in Developing Learning Media - Selvi Dwi Hartiyani; Landung Sudarmana (Jurnal Media dan Teknologi Pendidikan, 2025)
The development of the world of education, learning in the future will not only be about pedagogy and andragogy, but also include heutagogy and cybergogy, global and national conditions such as wars between countries and large-scale demonstrations if frequent and continuous, will affect learning conditions and learning outcomes. This study aims to implement active learning centered on students, with the background of changes in the learning paradigm that is centered on teachers with the industrial revolution 4.0. The ability or competence of teachers today is not only about pedagogy and andragogy, but also huetagogy, and cybergogy. This is very necessary because it is for sustainable learning and has an impact on the future of education. This research and development study uses APPED (Analysis and Initial Research, Design, Production, Evaluation and Dissemination). The data collection technique was carried out by filling out an instrument consisting of 30 questions with points 1-3 which aimed to determine the students' learning styles using visual, auditory or kinesthetic learning styles. After knowing the students' learning styles, learning and learning media were designed so that students play an active role in the learning process. Learning media was produced using Canva, Quizizz, Mentimeter, and EdPuzzle, and evaluated and disseminated. Three classes, 10 students from each class, were sampled, resulting in seven active students with a score of 80% and three active students with a score of 60%. Therefore, the implementation of active learning using these learning media techniques can be considered successful.